2018
DOI: 10.1002/msc.1357
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of diagnostic agreement rates between advanced practice physiotherapists and paediatric orthopaedic consultants for children with musculoskeletal complaints

Abstract: This was the first study to evaluate diagnostic agreement rates between APPs and orthopaedic consultants, the appropriateness of onward referral by APPs and the SCR for paediatric musculoskeletal patients referred from an APP clinic. Good to excellent diagnostic agreement was observed for routine elective paediatric orthopaedic patients, in tandem with agreement levels reported in the adult literature. The study demonstrates that APPs are clinically effective in the diagnosis and onward referral of paediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…The participants concurred on the competency of the APP to manage patients independently and make accurate diagnoses, echoing previous findings by O'Sullivan and Doody (2014). Although these perceptions of the consultants are experiential, they mirror previous evidence reporting high correlation between APPs and consultants in terms of musculoskeletal patients' diagnosis and management (Marks et al, 2016; Ó Mír et al, 2018; Oakley & Shacklady, 2015; Thompson et al, 2017; Trøstrup et al, 2017). Similar to the way our consultants describe the ability to make clinical decisions as an almost nonconcrete trait, Thompson et al (2017)point out that although APPs have demonstrated excellent levels of clinical judgement, the process of their clinical decision‐making and the training/experience necessary to reach this level is not yet fully understood.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The participants concurred on the competency of the APP to manage patients independently and make accurate diagnoses, echoing previous findings by O'Sullivan and Doody (2014). Although these perceptions of the consultants are experiential, they mirror previous evidence reporting high correlation between APPs and consultants in terms of musculoskeletal patients' diagnosis and management (Marks et al, 2016; Ó Mír et al, 2018; Oakley & Shacklady, 2015; Thompson et al, 2017; Trøstrup et al, 2017). Similar to the way our consultants describe the ability to make clinical decisions as an almost nonconcrete trait, Thompson et al (2017)point out that although APPs have demonstrated excellent levels of clinical judgement, the process of their clinical decision‐making and the training/experience necessary to reach this level is not yet fully understood.…”
Section: Discussionsupporting
confidence: 76%
“…The lead researcher (M.O.M) works as an APP in a tertiary paediatric orthopaedic hospital and acknowledges that in evaluating the APP role in paediatric orthopaedics, she is, in part, evaluating her own practice (Ó Mír, O'Sullivan, Lennon, & Blake, 2018). Strategies undertaken to minimise bias included the lead researcher not interviewing consultants she worked with and reflection and critical discussion amongst the researchers to facilitate reflexivity.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have demonstrated that the diagnostic accuracy of APPs is equal to that of physicians and surgeons when managing patients with MSK disorders (Burn and Beeson, 2014;Chartered Society of Physiotherapy, 2016;Mír M, O'Sullivan, Lennon, and Blake, 2018). The findings from our study suggest that most APPs have over 15 years of clinical experience, of which a minimum of 5 years is spent in MSK practice.…”
Section: Discussionsupporting
confidence: 53%
“…The findings from our study suggest that most APPs have over 15 years of clinical experience, of which a minimum of 5 years is spent in MSK practice. The years of clinical experience of the practitioner could explain their level of diagnostic accuracy and agreement, as suggested by the published studies (Burn and Beeson, 2014;Chartered Society of Physiotherapy, 2016;Mír M, O'Sullivan, Lennon, and Blake, 2018). The revised competency and capability framework reflects the need for advanced clinical knowledge and skills, including training traditionally undertaken by other medical disciplines such as orthopedics, rheumatology, radiology and laboratory medicine.…”
Section: Discussionmentioning
confidence: 99%
“…Anecdotal evidence indicates that this issue continues, as many parents remain reluctant to take their children to the hospital despite evidence that COVID-19 rarely causes significant illness in this age group. Fortunately, most musculoskeletal problems that cause concern in preschoolers (e.g., bowlegs, knock knees, flat feet) are part of normal development; they are the so-called “normal variants” that resolve themselves without treatment [ 121 ]. In these cases, no harm will arise from delays, in addition to ongoing parental anxiety.…”
Section: Musculoskeletal Perspectivementioning
confidence: 99%